Boni et mali principes, un empire en jeu(x) : discours, figures et postures impériales - Stéphane Benoist (Kentron, 2022)
The Imperial biographies written between the Antonine 2nd century CE to the Theodosian end of the 4th c. and the beginning of the 5th c. deliver an original approach of the Imperial characters. We can analyze those portraits through the conception of a festivals and ceremonies universe to understand the so-called “Imperial discourse” created within the emperors’ entourage, from Augustus to Diocletian and Constantine who were fictitious addressees of various uitae principum from the Historia Augusta. Suetonius, the so-called Historia Augusta and the late abbreviators present many examples of a systematic practice to consider Principates by using private behaviors and public politics, ludi and spectacula, passions and personal customs, in order to characterize the various Imperial personae and sharing between good and bad emperors. Even if portraits are not univocal and can present ambiguous situations, they aim to reveal social troubles and the limits of peculiar conceptions of the statio principis when frontiers disappear and the tradition is questioned, between norms and excess.